The evolution of Homo Discens: natural selection and human learning - Osmo Kivinen; Tero Piiroinen (Blackwell Publishing Ltd, 2022)
This article takes an evolutionary “reverse engineering” standpoint on Homo discens, learning man, to track down the (learning) mechanisms that played a pivotal role in the natural selection of human being. The approach is “evolutionary sociological”—as opposed to gene‐centred or psychologising—and utilises notions of co‐evolutionary organism–environment transactions and niche construction. These are compatible with a Deweyan theory of action, which entails that in action one cannot but learn and one can only learn in action. Special attention is paid to apprentice‐like learning‐by‐doing peculiar to human socio‐cultural niches since the Pleistocene, which has permitted each subsequent generation to learn the many habits and skills needed in utilising the affordances of action that constitute their ecological niche. Affordances and actions have changed over the history of human–environment transactions, but the core mechanisms of human learning have not changed much. It is increasingly important to appreciate these mechanisms now in the global age “knowledge society,” which is in a way similar to the Pleistocene era: characterised by uncertainty and life‐determining problem‐situations without any ready‐made solutions, it calls for capacities to adapt to changing circumstances, and thus apprentice‐like learning in action supported by savvy epistemological engineering of learning environments.